Target Therapies for Systemic Mastocytosis: An Update - Mariarita Sciumè; Claudio De Magistris; Nicole Galli; Eleonora Ferretti; Giulia Milesi; Pasquale De Roberto; Sonia Fabris; Federica Irene Grifoni (Pharmaceuticals, 2022)
Systemic mastocytosis (SM) results from a clonal proliferation of abnormal mast cells (MCs) in extra-cutaneous organs. It could be divided into indolent SM, smoldering SM, SM with an associated hematologic (non-MC lineage) neoplasm, aggressive SM, and mast cell leukemia. SM is generally associated with the presence of a gain-of-function somatic mutation in KIT at codon 816. Clinical features could be related to MC mediator release or to uncontrolled infiltration of MCs in different organs. Whereas indolent forms have a near-normal life expectancy, advanced diseases have a poor prognosis with short survival times. Indolent forms should be considered for symptom-directed therapy, while cytoreductive therapy represents the first-line treatment for advanced diseases. Since the emergence of tyrosine kinase inhibitors (TKIs), KIT inhibition has been an attractive approach. Initial reports showed that only the rare KITD816V negative cases were responsive to first-line TKI imatinib. The development of new TKIs with activity against the KITD816V mutation, such as midostaurin or avapritinib, has changed the management of this disease. This review aims to focus on the available clinical data of therapies for SM and provide insights into possible future therapeutic targets.